PENETAPAN KADAR FLAVONOID EKSTRAK ETANOL DAN ETIL ASETAT DAUN MANGGIS (Garcinia mangostana L.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Ginting, Junius Gian; Simanjuntak, Helen Anjelina; Purba, Hermawan (LPPM Universitas Bakti Tunas Husada, 2024)
In traditional medicine, mangosteen leaves (Garcinia mangostana L.) are useful in treating diabetes, hypertension, diarrhea, dysentery, and urinary tract problems. The study aims to determine the levels of flavonoids in mangosteen leaves with 96% ethanol and ethyl acetate. The total flavonoid content was determined by UV-Vis spectrophotometry, and the maceration process on the extract using 96% ethanol and ethyl acetate. The results of phytochemical screening of mangosteen leaf extract with 96% ethanol and ethyl acetate contained flavonoids, alkaloids, saponins, tannins and steroids/triterpenoids. The total flavonoid content in 96% ethanol solvent was 50.110 mgQE/gram extract and the total flavonoid content in ethyl acetate solvent was 118.773 in the extract. Ethyl acetate solvent is more effective in attracting flavonoid compounds in mangosteen leaves.